种具有高强度、高耐疲劳性的PC/ABS合金材料及其制备方法 (2018)
本发明涉及种具有高强度、高耐疲劳性的PC/ABS合金材料及其制备方法，所述PC/ABS合金材料包括：PC树脂：30～80，ABS树脂：20～70，反应挤出添加剂：1～10；抗氧剂0.1～1，润滑剂0.1～1；所述反应型挤出添加剂为含甲基丙烯酸缩水甘油酯(GMA)功能单体的苯乙烯-丙烯腈共聚物。与现有技术相比，本发明所提供的PC/ABS合金，利用反应挤出增加了PC/ABS体系中分子链的缠结程度，在遭受外力时分子链不容易遭受破坏，通过注入超临界流体，不仅促进反应挤出添加剂的分散，同时降低了熔体在反应挤出过程中的温度，控制反应程度，避免体系黏度过大，获得了高强度、高耐疲劳性PC/ABS合金材料。 The invention relates to a PC/ABS alloy material being high in strength and fatigue resistance and a preparation method thereof. The PC/ABS alloy material includes: 30-80 parts of PC resin, 20-70 parts of ABS resin, 1-10 parts of a reactive extrusion additive, 0.1-1 part of an antioxidant and 0.1-1 part of a lubricant, wherein the reactive extrusion additive is a styrene-acrylonitrile copolymer that contains a glycidyl methacrylate (GMA) functional monomer. Compared with the prior art, the PC/ABS alloy material is increased in entanglement degree of a molecular chain in the PC/ABS system through reactive extrusion, so that the molecular chain is not liable to damage under external force. Through injection of a super